Combining ability analysis for yield and its contributing attributes in Field Pea (Pisum sativum L.) - Singh, Manender; Malik, Sunil; Kumar, Mukesh; Rathi, Y.S.; Kumar, Sanjiv; Dev, Pavitra (Annals of Agricultural Research, 2016)
Combining ability analysis for yield and its contributing attributes was conducted at Horticulture Research Centre of Sardar Vallabhbhai Patel University of Agriculture & Technology, Meerut (U.P.), involving nineteen parents (Sixteen lines and three testers) of pea in line x tester fashion. The mean square for both general combining ability and specific combining ability were significant for all the forty eight hybrids with nineteen parents. Both additive and non-additive gene actions were involved in the inheritance of traits. In general, high magnitude of specific combining ability variance depicted the greater role of non-additive gene action in the inheritance of all the characters study. Parents EC-322748, Rachna and Pant P-5 have been identified as good general combiners on the basis of per se performance as well as combining ability analysis for seed yield. The crosses EC-322748 X Pant P-5, JP-4 X HUDP-15, EC-324705 X HUDP-15, EC328758 X HUDP-15, P185 X HUDP-15 and IPE-99-25 X HUDP-15 were the most desirable specific combinations for seed yield per plant and other contributing traits such as days to maturity, plant height, pods per plant, productive branches per plant, 100 seed weight, biological yield per plant.